2016
DOI: 10.1111/cpf.12380
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood flow changes in response to postexercise cold water immersion

Abstract: This study compared the effect of postexercise water immersion (WI) at different temperatures on common femoral artery blood flow (CFA), muscle (total haemoglobin; tHb) and skin perfusion (cutaneous vascular conductance; CVC), assessed by Doppler ultrasound, near-infrared spectroscopy (NIRS) and laser Doppler flowmetry, respectively. Given that heat stress may influence the vascular response during cooling, nine men cycled for 25 min at the first ventilatory threshold followed by intermittent 30-s cycling at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
2
21
3
1
Order By: Relevance
“…Similar results have been reported previously (15,44) and align with recent meta-analyses which reported that CWI has a trivial-small effect on reducing lactate 277 (Hedges' g < 0.3) (16) and CK (Hedges' g < 0.1 -0.2) (16,22) efflux in to the blood post-278 exercise. It has been proposed that efflux rates may be sensitive to blood flow changes (22) and 279 although regional blood flow was not measured in the present study it is likely that blood flow 280 disturbances were greater in CWI5 than CWI14 and in both CWI trials compared to CON (7).…”
Section: The Effect Of Cwi On Physiological Markers Of Recovery 268mentioning
confidence: 73%
“…Similar results have been reported previously (15,44) and align with recent meta-analyses which reported that CWI has a trivial-small effect on reducing lactate 277 (Hedges' g < 0.3) (16) and CK (Hedges' g < 0.1 -0.2) (16,22) efflux in to the blood post-278 exercise. It has been proposed that efflux rates may be sensitive to blood flow changes (22) and 279 although regional blood flow was not measured in the present study it is likely that blood flow 280 disturbances were greater in CWI5 than CWI14 and in both CWI trials compared to CON (7).…”
Section: The Effect Of Cwi On Physiological Markers Of Recovery 268mentioning
confidence: 73%
“…Overall, the increase in Δtotal[Hb+Mb] muscle in the TA muscle was a result of the Δoxy[Hb+Mb] muscle increase during the CCWI, and this response was a result of both the Δoxy[Hb+Mb] muscle and Δdeoxy[Hb+Mb] muscle during the recovery period. Choo et al (2018b) reported that the skin blood flow had notably less influence on the total[Hb+Mb] signal during the recovery after cooling compared to a non-cooling recovery. However, our findings regarding the Δtotal[Hb+Mb] muscle kinetics differed, and they indicate that CO 2 could influence the muscle blood flow increase.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the improved performance could potentially be explained by the reduced sensation of DOMS (Figure 3 ), independent of muscle damage. Indeed, perception of DOMS seems to be important to the recovery of exercise performance, as muscle pain independent of muscle damage has been shown to impair force generating capacity ( Graven-Nielsen et al, 2002 ) Accordingly, CWI has been suggested to modulate the sensation of DOMS, and by extension muscle function, through limiting oedema ( Ihsan et al, 2013 ; Choo et al, 2016 ) and/or through activating cutaneous receptors that mediate analgesia ( Knowlton et al, 2013 ; Ihsan et al, 2016 ). Counterintuitive to the notion of recovery, CWI resulted in moderate and large decrements in POST-R for 5-m and 10-m sprint performances, respectively (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%